Juvenile dermatomyositis with central nervous system involvement: two case reports from a retrospective single-center cohort, with literature review - Yang, Ling; Guan, Wanzhen; Liu, Haimei; Li, Yifan; Gong, Yinv; Lv, Qianying; Zeng, Qiaoqian; Wei, Qijiao; Zhang, Xiaomei; Chen, Weiming; Chen, Chao; Sun, Li (Frontiers in Pediatrics, 2024)
Background: Juvenile dermatomyositis (JDM) is a systemic autoimmune disease primarily involving the muscles and skin; it can also affect the central nervous system (CNS). The relevant literature provides limited information regarding the characteristics of JDM with CNS involvement.We reviewed patients with JDM who were hospitalized at our center between January 2016 and August 2023, with a focus on those with CNS involvement. The aim was to provide detailed case reports on these patients, and to summarize the relevant literature about the characteristics of similar cases.Results: Among 193 hospitalized patients with JDM, two (1.03%) had CNS involvement. Two patients, a 5.5-year-old girl and an 11-year-old boy, were admitted with severe proximal muscle weakness and seizures, and presented with active cutaneous vasculitis. Both were ultimately diagnosed with JDM, with CNS involvement. Both patients had confirmed presence of anti-NXP antibody through myositis-specific antibody analysis. Additionally, they all exhibited hyperferritinemia and thrombocytopenia. Salvage therapies like intravenous methylprednisolone (IVMP) pulse therapy and/or plasma exchange were administered successfully. At final follow-up, both patients had achieved complete clinical response and full neurological recovery. Our literature review identified nine similar case studies. CNS involvement usually occurred within the first 10 months of the disease course, and most of these patients had fatal outcomes, with a mortality rate of 66.6% (6/9). Including the two patients described herein, the median age for disease onset is 10.5 years (range 4-17 years), and the male:female ratio is 6:5. Seizures are the most common neurological symptom, accompanied by active cutaneous vasculitis. The brain biopsies showed two distinct pathological presentations: one was central nervous system vasculitis, and the other was cerebral macrophage activation syndrome.Conclusions: CNS involvement is a rare but life-threatening JDM complication. Herein, our cases and the literature indicate that it typically occurs within the first 10 months of the disease course and manifests as seizures, often accompanied by active cutaneous vasculitis, with fatal outcomes. Timely implementation of salvage therapies, like IVMP pulse therapy and plasma exchange, may significantly impact patient outcomes.